Implementasi Metode Technique for Order of Preference by Similarity to Ideal Solution Untuk Prioritasasi Objek Wisata - Andi Wibowo; Ardhin Primadewi; Emilya Ully Artha (Journal of Information System Research (JOSH), 2025)
Tourist attractions are anything that draws people's attention to visit a particular destination. Magelang Regency, Central Java, has significant natural tourism potential, especially in mountainous areas like Mount Sumbing, which attracts both domestic and international tourists. However, many tourists face difficulties in choosing a destination that aligns with their preferences. This research aims to develop and implement the TOPSIS method to assist tourists in selecting the best attractions in the Mount Sumbing area based on various criteria such as distance, facilities, cost, comfort, and scenery. The TOPSIS method (Technique for Order of Preference by Similarity to Ideal Solution) was chosen for its ability to evaluate alternatives by comparing positive and negative ideal solutions, providing objective and accurate ranking results. By applying the TOPSIS method to the evaluation of tourism alternatives, preference values are calculated to determine the best option. The results show that alternative 3 Nepal Van Java has the highest preference value, which is 0.7920. The findings provide relevant rankings of tourist attractions, offering valuable guidance for tourists and tourism managers in optimizing the tourism experience in the area.